SHARIA BANKING CONTRIBUTION TO INDONESIA'S ECONOMIC GROWTH DURING PANDEMIC - Sandi Mulyadi; Asep Suryanto (UIN Mataram, 2022)
The background of the research is the issue of research on the growth conditions of Islamic banks in Indonesia during the pandemic to describe the contribution of Islamic banks to economic growth in Indonesia during this pandemic, the variables used are third-party funds, financing, total assets of Islamic banking and the pandemic. The research method uses quantitative by analyzing secondary data which is processed using Eviews 10 with the VECM method and using quarterly time-series data from 2010-2021. The results of the data processing using the VECM method showed several findings, namely: the variables of third-party funds, Islamic banking financing, and the pandemic had a negative effect and total Islamic banking assets had a positive effect on economic growth for a long time. Meanwhile, the results of the IRF test show that the response to economic growth in responding to shocks to these variables was unstable for 60 periods with contributions from third-party funds (4%), financing (7%), total Islamic banking assets (24%) and pandemics (6%).